Metodologi Ijtihad Mazhab Indonesia: Menelusuri Pemikiran Ushul Fikih Hazairin - Agus Moh Najib (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2016)
Hazairin is one of the pioneers who initiated the importance of Islamic law with Indonesian pattern. Even, he viewed the importance of the new school (mazhab) in Islamic law, namely the Indonesian mazhab. However, Hazairin’s thought on the methodology of ijtihad, as a basis for the establishment of a school of Islamic law, has not been widely studied. His thought which was more studied is the idea of the Indonesia mazhab and also about inheritance law. This article specifically explores the framework of Usul Fiqh proposed by Hazairin. Epistemologically, the main topic of Usul Fiqh is about the sources of Islamic law and the method of how to formulate Islamic law from the source. Therefore, this article examines Hazarin’s thought about the two things, namely the sources of Islamic lawand its legal formulation method. From the study done, both on the sources of law and Islamic law formulation method, Hazarin put the role of ulu al-amri (government, policy makers) in a strategic position. The method of legal formulation done by ulu al-amrirequires musyawarah(discussions), which involves jurists and other relevant scientific experts (collective ijtihad). Results of ijtihad decided by ulu al-amri will automatically become binding formal rules of law, so that if the resultsof ijtihad is followed and practiced by the public widely, it will become a new school of Islamic law, namely the Indonesian mazhab.